How Extensively do Teachers Train Students' Metacognition Abilities in Physics Learning in High School? - Alpindo, Okta; Istiyono, Edi; Widihastuti, Widihastuti (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
Metacognition refers to the capacity to comprehend and regulate one's own cognitive processes. By cultivating students' metacognitive skills in physics education, they will acquire the ability to understand and govern their own thinking. This, in turn, will enhance the effectiveness of physics instruction by fostering student engagement and enabling them to rectify their own errors. However, previous studies have revealed a scarcity of physics teachers who integrate metacognitive training into their teaching practices. Thus, the aim of this research is to investigate the extent to which high school physics teachers in the Riau Islands Province engage in metacognitive training for their students. Employing a qualitative approach with a phenomenological method, data was collected through interviews conducted with physics teachers from local high schools. This study's participants are physics teachers in the Kepulauan Riau Province. There are a total of 25 physics teachers participating in the study. The sampling technique employed in this research is purposive sampling. During these interviews, the researchers posed open-ended questions to elicit insights into physics teachers' experiences with the cultivation of metacognitive skills in their students during physics lessons. According to the study's findings, physics teachers in the Riau Islands Province are indeed training their students in indicators of metacognitive abilities. However, we observed that some teachers remain unaware that the exercises they assign inherently serve as indicators of metacognitive skills. This lack of awareness is attributed to a deficient understanding among teachers regarding the nature of metacognition.